Nutrition reaction of different varieties of winter wheat (Triticum aestivum L.) bred in Karcag - Czimbalmos, Ágnes; Szűcs, Lilla; Zsembeli, József (Acta Agraria Debreceniensis, 2016)
In our study the nutrition reaction of four varieties of winter wheat (KG Bendegúz, KG Kunhalom, KG Kunkapitány, KG Széphalom) has been investigated. In the experiment the effect of twenty different nutrition doses on the yield and thousand kernel weight of the wheat varieties has been studied. Significant difference could be figured out among the yield and thousand kernel weight of the wheat varieties, so the choice of the proper variety determines the quantity of yield. KG Kunkapitány had the highest yield, while KG Széphalom had the highest thousand kernel weight in the experiments.Investigating the effect of the nutrients on the yield the conclusion was that all nitrogen doses had significant yield increasing effect compared to the untreated plots, but among the 40, 80 and 120 kg ha-1 doses there was no statistical difference. In the case of phosphorus the 40 kg ha-1 dose showed statistically verifiable increase of the yield, while potassium doses have no influence on the yields. The thousand kernel weights reached the maximum values where the highest nutrient doses were applied.